EPISTEMIC MODALITY OF THE RUTHENIAN DISCOURSE PRACTICES IN THE EARLY MODERN PERIOD - Nika, O. (Linguistic and Conceptual Worldviews, 2020)
The article analyzes the influence of epistemic modality on the change of discourse practices in Ukraine in the early Modern period. It explores discourse practices of the 16th and 17th centuries in their dynamic state applying the principles of ‘cultural knowledge’ (the term introduced by M. Foucalt). The paper discusses the common and distinctive features of realizing epistemic modality in polemical and homiletic discourses. The author argues that they are new discourse practices, which appeared as a result of compelling social needs arising in the 16th and 17th centuries, while the functions of the literary language of the time, the Ruthenian language, enhanced. The study shows that in the discourse practices, religious notions were conceived through demonstrating epistemic states of the author / readers that reveal the subjectivity / intersubjectivity in conception, interpretation, and understanding the postulates of faith. The paper proves that epistemic modality is interlinked with certainty, evidentiality, and inferentiality. The article focuses on the epistemic verbs знати (to know), відати (to be aware), розуміти (to understand) which explicate the epistemic modus of the author in these discourse practices and perform phatic and persuasive functions. Thus, the paper considers discursive features of the phraseological unit дати знати (let sb know), signaling the transition from a quotation to an inference, an explication of the message of the preacher. The study also presents grammatical modifications of the phraseological unit: the past tense forms (давал/дал знати), the impersonal form -но (давано знати), participle (даючи знати). The author establishes the link between the epistemic вѣдат with indirect evidentiality and certainty. The author also shows the dominant of the epistemic verb розумѣти in the discourse of the polemists and preachers of the early Modern period.